Reconstructing the Meaning of Polygamy in the Context of Gender Relations: Study of Surah an-Nisā’ [4]: 3 Using the Ma‘nā-Cum-Maghzā Approach - Rokhman, Mokh. Fatkhur; Umami, Khoirul; Hakim, Muhammad Naufal (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2024)
Reconstructing the Meaning of Polygamy in the Context of Gender Relations Study of Surah an-Nisā’ [4]: 3 Using the Ma‘nā-Cum-Maghzā Approach. This article aims to reconstruct the meaning of polygamy in Surah an-Nisā’ verse 3 within the context of gender relations. To achieve this goal, this research employs a deconstructive paradigm using a hermeneutical approach, ma‘na-cum-maghzā method by Sahiron Syamsuddin, and feminist theory as analytical tools. The study yields two main findings: (1.) Universally, the primary message (maghzā) contained in Surah an-Nisā’ verse 3 emphasizes the importance of gender justice for women. Thus, in a broader context, the maghzā of this verse rejects any actions that subordinate and negate women’s rights, Thus, from here, this research aligns with the opinion of Muhammad Irsad.; (2.) When the universal moral value of Surah an-Nisā’ verse 3, stating the importance of gender justice, is recontextualized into the specific context of polygamy, this research aligns with the view that the primary directive in this verse is monogamy accompanied by efforts to build a harmonious and quality Islamic family. Polygamy, on the other hand, can only be practiced under highly specific and urgent conditions. Additionally, this study rejects actions that use this verse as a legitimization for patriarchal views that tend to relegate women to a secondary class in society.